The Situation in Northeastern Armenia in the First Quarter of the 18-th Century - Yesayan, Andranik (History and Culture, 2021)
After the Persian-Ottoman Wars from the 17th century to the 1730’s a favorable environment for peaceful construction and economic development was created in Northeast Armenia. As a result, some population immigration was observed here from other sides of Armenia.. New monasteries and churches were built in the region. Situation changed when the Sefevids began to weaken in the latter part of the century. For the preventation the destruction of empire the Safavid government imposed heavier taxes, which made the lives of the population unbearable. Turkey and Russia begun to take advantage of the opportunity. In parallel the settlements of northeastern Armenia began to be plundered by lezgins. Their troops regularly crossed the Kur River and destroyed the Armenian settlements. This actions were inspired by Turkey, because they wanted to made their further invasion eaisyer. The Ottoman Empire, agreed with the Russian side, was able to occupy the entire region in 1725. These events made a huge difference to the demographic image of the region.